Acceptability and Ease of Use of an Educational Website among Women, Infants, and Children Program Participants in Puerto Rico: A Pilot Study - Kallis, Maria G.; Campos, Maribel; Helen-Mays, Mary; Palacios, Cristina (Puerto Rico Health Sciences Journal, 2023)
Objective: To evaluate a website for an educational intervention among participants of the Baby-Act Trial. Baby-Act is a community-based intervention to prevent infant obesity by promoting physical activity, sleep, and healthy eating behaviors in Women, Infants, and Children (WIC) program participants in Puerto Rico. The intervention was designed to be delivered through a mobile application, but after the study was launched, participants reported many difficulties, and an alternative educational platform was developed. Methods: Participants of the WIC program completed a face-to-face structured interview consisting of several open-ended questions. After completing the interview, they were instructed on how to access the newly developed webpage and completed the lessons found therein. Then followed a survey that explored the overall experience. Results: Nine participants were interviewed; they all agreed that the website was easy to access, registration was simple, and the webpage was clear; 8 were able to complete at least 1 lesson (1 participant had a very poor signal), and all 9 reported being confident in using the webpage and stated they would use it again. Conclusion: The study participants found this website to be user-friendly and a viable alternative for future educational intervention delivery to WIC participants.